Enhanced osmotic energy conversion through bacterial cellulose based double-network hydrogel with 3D interconnected nanochannels. (1st April 2023) - Sun, Zhe; Kuang, Yudi; Ahmad, Mehraj; Huang, Yang; Yin, Sha; Seidi, Farzad; Wang, Sha
Abstract: Hydrogel with 3D networks have shown great potential for ion transportation and energy conversion. However, the micron size pores of hydrogel greatly limit the ion selectivity and energy conversion performance. Here, we report a bacterial cellulose (BC) derived hydrogel membrane with double-network (DN) and tailored ion transport channels by rationally filling acrylic acid (AAc)- co -acrylamide (AAm)- co -methyl methacrylate (MMA) polymers into BC hydrogel micropores. Fabricated AAM/BC DN hydrogel membrane displays a unique hierarchical interconnected porous structure and 3D cation transport channels. From the results, the maximum power density reached up to 7.63 W·m −2 at 50-fold salinity gradient under alkaline conditions (pH 11). Interestingly, the power density of 45.5 W·m −2 was achieved through acid-base neutralization reaction. Furthermore, hydrogel successfully obtained a power density of 28.4 W·m −2 from a mixed system of paper black liquor wastewater/seawater. The results of this investigation suggested the enormous potential of BC-based nanofluidic membrane in sustainable osmotic energy conversion. Graphical abstract: Based on the unique hierarchical interconnected porous structure and 3D cation transport channels of the AAM/BC DN hydrogel membrane, its nanofluidic generator exhibits excellent pH-dependent osmotic energy conversion performance. Unlabelled Image Highlights: AAM/BC DN hydrogels with interconnected 3D nanochannels were prepared. The combination of BC and AAM hydrogel can promote output power density. The AAM/BC DN hydrogel achieves high power density in black liquor wastewater. Our work offers new opportunity for fabricating high-performance nanogenerators.